Early Maternal Sensitivity and Teacher–Student Relationship Quality Across Grade School: Enduring or Transient Associations?. Issue 4 (21st October 2019) - Magro, Sophia W.; Fraley, R. Chris; Roisman, Glenn I.
Abstract : Although teacher–student relationships are assumed to in part reflect early caregiving quality, their social provisions also undergo notable normative change over the course of primary school, shifting from a secure base for social exploration to an instrumental relationship centered on achieving academic goals. This report leveraged prospective, longitudinal data from the Study of Early Child Care and Youth Development ( N = 1, 306, 52% male, 77% White/non‐Hispanic) to investigate whether the association between early caregiving and subsequent teacher–student relationship quality remains stable or diminishes in magnitude over time. Associations between early maternal sensitivity and teacher–student closeness faded from Kindergarten to Grade 6. In contrast, associations between early caregiving and teacher–student conflict endured and were partially accounted for by child externalizing problems.